Điều khiển trên cơ sở lọc hai mức với mô hình nhiễu quan sát mở rộng - Lân, Vũ Như; Hưng, Vũ Chấn; Phu, Đặng Thành (Journal of Computer Science and Cybernetics, 2016)
Models of observation noise are interested by many authors, but these models are not studied on complete extention. In this paper by using two-level filter and extended model of the noise, an investigation of the control model is established.